IPSAS IMPLEMENTATION AND PERSPECTIVES FOR EPSAS IMPLEMENTATION AT THE EUROPEAN UNION LOCAL GOVERNMENT LEVELS - CRISAN, Andrei-Razvan; NISTOR, Cristina Silvia; TIRON-TUDOR, Adriana; OPRISOR, Tudor (Studia Universitatis Babeș-Bolyai Negotia, 2016)
Nowadays, the implementation of the IPSAS (International Public Sector Accounting Standards) and the perspectives for EPSAS (European Public Sector Accounting Standards) implementation at the European Union level is a severe problem. The implementation of IPSAS could be the earliest step in the EPSAS implementation that is considered beneficial to the particular needs of the European Union. Within the present paper, in order to assess the level of harmonization at the local level, the Herfindahl index was used. For our study, we considered the European Union cities with a population larger than 300,000 inhabitants, using the financial reports published by these municipalities on their websites. The results of the study indicate a high degree of dispersion regarding the items disclosed by the local governments in their financial statements, taking IPSAS 1 and IPSAS 2 as a benchmark. On the other hand, the results reveal the fact that the English municipalities disclose to the greatest extent the items requested by IPSAS 1 and IPSAS 2.